Argonaute5 and its associated small RNAs modulate the transcriptional response during the rhizobia-Phaseolus vulgaris symbiosis - Sánchez-Correa, María del Socorro; Isidra-Arellano, Mariel C.; Pozas-Rodríguez, Eithan A.; Reyero-Saavedra, María del Rocío; Morales-Salazar, Alfredo; del Castillo, Sarah Melissa Lugo-Caro; Sanchez-Flores, Alejandro; Jiménez-Jacinto, Verónica; Reyes, Jose L.; Formey, Damien; Valdés-López, Oswaldo (Frontiers in Plant Science, 2022)
Both plant- and rhizobia-derived small RNAs play an essential role in regulating the root nodule symbiosis in legumes. Small RNAs, in association with Argonaute proteins, tune the expression of genes participating in nodule development and rhizobial infection. However, the role of Argonaute proteins in this symbiosis has been overlooked. In this study, we provide transcriptional evidence showing that Argonaute5 (AGO5) is a determinant genetic component in the root nodule symbiosis in Phaseolus vulgaris. A spatio-temporal transcriptional analysis revealed that the promoter of PvAGO5 is active in lateral root primordia, root hairs from rhizobia-inoculated roots, nodule primordia, and mature nodules. Transcriptional analysis by RNA sequencing revealed that gene silencing of PvAGO5 affected the expression of genes involved in the biosynthesis of the cell wall and phytohormones participating in the rhizobial infection process and nodule development. PvAGO5 immunoprecipitation coupled to small RNA sequencing revealed the small RNAs bound to PvAGO5 during the root nodule symbiosis. Identification of small RNAs associated to PvAGO5 revealed miRNAs previously known to participate in this symbiotic process, further supporting a role for AGO5 in this process. Overall, the data presented shed light on the roles that PvAGO5 plays during the root nodule symbiosis in P. vulgaris.